Stimulation of P2Y11 receptor modulates cardiac fibroblasts secretome toward immunomodulatory and protective roles after Hypoxia/Reoxygenation injury. (August 2018) - Lefort, Claudie; Benoist, Lauriane; Chadet, Stéphanie; Piollet, Marie; Heraud, Audrey; Babuty, Dominique; Baron, Christophe; Ivanes, Fabrice; Angoulvant, Denis
Abstract: Cardiac fibroblasts are important regulators of myocardial structure and function. Their implications in pathological processes such as Ischemia/Reperfusion are well characterized. Cardiac fibroblasts respond to stress by excessive proliferation and secretion of pro-inflammatory cytokines and other factors, e.g. ATP, leading to purinergic receptors activation. P2Y11 receptor (P2Y11R) is an ATP-sensitive GPCR playing an immunomodulatory role in human dendritic cells (DC). We hypothesized that P2Y11R stimulation modulated the pro-inflammatory responses of human cardiac fibroblasts (HCF) to Hypoxia/Reoxygenation (H/R) mainly by acting on their secretome. P2Y11R stimulation in HCF at the onset of reoxygenation significantly limited H/R-induced proliferation (−19%) and pro-inflammatory cytokines and ATP secretion (−44% and −83% respectively). Exposure of DC to HCF secretome increased their expression of CD83, CD25 and CD86, suggesting a switch from immature to mature phenotype. Under LPS stimulation, DC had a pro-inflammatory profile (high IL-12/IL-10 ratio) that was decreased by HCF secretome (−3, 8-fold), indicating induction of a tolerogenic profile. Moreover, P2Y11R inhibition in HCF led to high IL-12 secretion in DC, suggesting that the immunomodulatory effect of HCF secretome is P2Y11R-dependant. HCF secretome reduced H/R-induced cardiomyocytes death (−23%) through RISK pathway activation. P2Y11R inhibition in HCF induced a complete loss of HCF secretome protective effect, highlighting the cardioprotective role of P2Y11R. Our data demonstrated paracrine interactions between HCF, cardiomyocytes and DC following H/R, suggesting a key role of HCF in the cellular responses to reperfusion. These results also demonstrated a beneficial role of P2Y11R in HCF during H/R and strongly support the hypothesis that P2Y11R is a modulator of I/R injury. Highlights: P2Y11R stimulation decreases H/R-induced proliferation of HCF. P2Y11R-stimulated HCF secretome decreases inflammatory profile of DC. P2Y11R-stimulated HCF secretome protects cardiomyocytes from lethal H/R injury. P2Y11R and HCF orchestrate cardiac cellular responses to H/R.